The Effect of Consumer Behavior and Service Quality on Consumer Decisions in Swosh Laundry - Nasrul Efendi; Pioner Pelawi; Suwianto Suwianto (Management Department Universitas Islam Negeri Sumatera Utara, 2023)
Maintaining consumer purchasing decisions is a challenging job especially in laundry service. The research objective was to determine the effect of consumer behavior and service quality on purchasing decisions. The sampling technique used was saturated sampling with a total sample of 120 respondents. The results showed that partially consumer behavior influences consumer purchasing decisions while service quality does not affect purchasing decisions. Furthermore, simultaneously consumer behavior and service quality influence purchasing decisions and a coefficient of determination of 0.17 indicates the contribution of consumer behavior and service quality to purchase decisions of 17%, while the remaining 83% is influenced by other variables.Keywords: Behavior, consumer decisions, service quality.